PS-P12-7: IDENTIFYING THE EVIDENCE-POLICY GAP IN TASK-SHARING WITH COMMUNITY HEALTH WORKERS FOR MANAGEMENT OF HYPERTENSION: A MIXED-METHOD STUDY. (January 2023) - Inagaki, Yoko; Matsushita, Kunihiro; Appel, Lawrence John; Perry, Henry B; Neupane, Dinesh
Abstract : Objective: Few studies are addressing the evidence-policy gap in task-sharing with community health workers (CHWs) to manage hypertension. We aimed to identify the gap by 1) performing a scoping review of peer-reviewed journals and 2) conducting in-depth interviews with key informants who have been involved in national CHW programs. Design and Methods: We searched PubMed for studies published from 2010–2021 following the PRISMA extension for scooping review guideline. We included all type of studies on task-sharing with CHWs for hypertension management. We extracted data on types, places, and the frequency of CHWs' activities and other relevant indicators. The primary outcomes were changes in systolic blood pressure (SBP), diastolic blood pressure (DBP), BP control, and medication adherence. In the corresponding countries, key informants with policy and implementation experience in national CHW programs were identified and interviewed. Result: A single reviewer screened 2, 316 records, of which 166 were assessed for eligibility, and 85 were included in the final review. There were 29 randomized controlled trials, 2 quasi-experimental trials, 11 pre-post studies, 2 prospective cohorts, 19 cross-sectional studies, and 22 qualitative studies. CHWs performed health education and BP measurement in 80% (60/75) and 63% (47/75) of studies, respectively. 89% (33/37) used digital BP device. Patients' home (64%, 47/71) was used the most with a median of one visit per month, followed by public space (11%, 8/71) and home/clinic (6%, 4/71). One CHW was responsible for an average of 116 participant with the range from 3 to 612. Significant reduction in SBP was seen in 56% (9/16) of the included trials. Eight informants from six countries (Brazil, India, Iran, Liberia, Thailand, Zimbabwe) participated in in-depth interviews. Brazil, India, Iran, Thailand, and Zimbabwe involved CHWs in health education, whereas only Thailand and Iran involved in BP measurement and both use manual BP devices. In these five countries, one CHW was responsible for an average of 1, 250 people with the range from 250 to 3, 000 in a national program. Conclusion: Despite clinically relevant BP reduction in CHW programs, there was suboptimal translation of this evidence into policy. The size of the population served per CHW and the type of BP device differed between research studies and national programs. Global health partners (i.e. those who generate evidence) and local governments need to work together to bridge the gap between evidence and policy. Figure 1: Forest plot of difference in systolic and diastolic blood pressure change in included studies.